Pneumococcal vaccination: an ongoing challenge (Actualizaciones en Sida e Infectología, 2025)
Pneumonia and invasive pneumococcal disease are associated with high morbidity and mortality, underscoring the importance of vaccination as a preventive strategy. In Argentina, since 2017, a sequential vaccination schedule with the 13-valent pneumococcal conjugate vaccine (PCV13) and the 23-valent pneumococcal polysaccharide vaccine (PPSV23) has been recommended for adults aged 65 years and older, as well as for younger adults with comorbidities. The introduction of the 20-valent pneumococcal conjugate vaccine (PCV20) to replace the sequential scheme, has not only the purpose to simplify vaccination schedules but also improve adherence.The aim of this study was to describe the pneumococcal vaccination status among hospitalized adults in a Hospital in Buenos Aires, Argentina. An observational, descriptive, cross-sectional study was conducted among individuals aged 18 years and older with an indication for vaccination between November 2024 and February 2025. Patients were classified into three groups: complete vaccination (VC), incomplete vaccination (VI), and unvaccinated (NV).A total of 137 patients were analyzed; 56.9% were male, and the mean age was 74.3 years. Of them, 88.3% were older than 65 years; among younger patients, the predominant comorbidities were diabetes, smoking, HIV, and cancer. Overall, 46 patients (33.5%) had complete vaccination, 14 (10.2%) had an incomplete schedule, and 77 (56.2%) had not received any dose. None had received PCV20, as it was not available at our center during the study period.Our findings suggest that pneumococcal vaccination coverage remains suboptimal. It is essential to obtain data from local healthcare centers to develop targeted strategies to improve it.
Keywords: Streptococcus pneumoniae; vaccination; adherence